Reinventing Caste: Indian Diaspora in Amitav Ghosh’s Sea of Poppies - Singh, Govt. (P.G.) College, Rajasthan, India, Omendra Kumar (Asiatic: IIUM Journal of English Language and Literature, 2012)
Profoundly engaged in capturing the outward flow of plantation diaspora from India in the nineteenth century, Amitav Ghosh’s Sea of Poppies (2008) focuses on one female girmitiya named Deeti, a high caste widow from Ghazipur in Uttar Pradesh, who elopes with an untouchable. Taking cue from the pages of Sir George Grierson’s diary, Ghosh recovers Deeti from history, not so much with the imagination of a novelist as with the instincts of an anthropologist. Devoted to reinvention, the novel tackles the loss of Deeti’s caste, its contested status in the migratory experience and its final recovery as a thematic concern. Though the traditional caste hierarchy was practically lost in the migratory process, I argue, it continued to exist in alternative form and only waited to be found in time. I also argue that the old Indian diaspora’s sentimental search for their ancestral roots in India is played out in the novel with the suggestion that their search may reveal some uncomfortable truth they would not like to know.